Traditional Chinese medicine Zhusha Anshen Wan: protective effects on liver, kidney, and intestine of the individual drugs using 1H NMR metabolomics - Wang, Dalu; Yu, Chong; Liu, Beixing; Wang, Haifeng (Frontiers in Pharmacology, 2024)
Introduction: Zhusha Anshen Wan (ZSASW) is a traditional Chinese medicine compound mainly composed of mineral drugs. In clinical practice, ZSASW did not show the toxicity of administering equal doses of cinnabar alone, suggesting that the four combination herbs in ZSASW can alleviate the damage of cinnabar. The effect of each herb on reducing the toxicity of cinnabar has not been fully explained. Methods: In our study, we utilized a metabonomics approach based on high-resolution 1H nuclear magnetic resonance spectroscopy to investigate the reduction of toxicity by each herb in ZSASW. Liver, kidney and intestinal histopathology examinations and biochemical analysis of the serum were also performed. Results: Partial least squares-discriminant analysis (PLS-DA) was conducted to distinct different metabolic profiles in the urine and serum from the rats. Liver and kidney histopathology examinations, as well as analysis of serum clinical chemistry analysis, were also carried out. The metabolic profiles of the urine and serum of the rats in the CGU (treated with cinnabar and Glycyrrhiza uralensis Fisch) and CCC (treated with cinnabar and Coptis chinensis French) groups were remarkably similar to those of the control group, while those of the CRG (treated with cinnabar and Rehmannia glutinosa Libosch) and CAS (treated with cinnabar and Angelica sinensis) groups were close to those of the cinnabar group. The metabolic profiles of the urine and serum of the rats in the CGU and CCC groups were remarkably similar to those of the control group, while those of the CRG and CAS groups were close to those of the cinnabar group. Changes in endogenous metabolites associated with toxicity were identified. Rehmannia glutinosa, Rhizoma Coptidis and Glycyrrhiza uralensis Fisch could maintain the dynamic balance of the intestinal flora. These results were also verified by liver, kidney and intestinal histopathology examinations and biochemical analysis of the serum. The results suggested that Discussion: The metabolic mechanism of single drug detoxification in compound prescriptions has been elucidated. Coptis chinensis and Glycyrrhiza uralensis serve as the primary detoxification agents within ZSASW for mitigating liver, kidney, and intestinal damage caused by cinnabar. Detoxification can be observed through changes in the levels of various endogenous metabolites and related metabolic pathways.